Graves-Basedow disease treated by complementary medicine leading to severe thyrotoxicosis – a case report - Klaudia Sapuła; Jakub Gołacki; Aleksandra Marczak; Michalina Hordejuk; Klaudyna Iwaszko-Sochal (Journal of Education, Health and Sport, 2022)
Graves' disease is a common cause of hyperthyroidism. Inadequate treatment or non-compliance can lead to serious complications, including thyroid storm.